Politics of security British and West German protest movements and the early Cold War, 1945 - 1970 - Nehring, Holger 1974- (Oxford historical monographs, 2013)
From war to post-war : security lost and found -- Identifying the protests and the protest-makers -- Political experiences and the security of community -- Organizing the extra-parliamentary politics of security -- 'Peace', the nation, and international relations -- Demonstrating security -- Openings : politics, culture, and activism in the 1960s -- Redefining solidarity -- Epilogue : redefining experiences